The Implementation Of Internet Small Computer System Interface (ISCSI) Protocol Based On Linux Centos As External Storage On Windows - Rion Gustardi; Herlina Latipa Sari; Hari Aspriyono (Jurnal Komputer, Informasi dan Teknologi, 2022)
This study aims to build a router in a computer network using a proxy, implement an external proxy server on a mikrotik router and implement caching on a local network. In this study, the action research method will be used, where the action research method can provide an overview of the stages of research that the writer needs, because the writer requires an analysis or diagnosis of the system that is currently running. The results of this study indicate that an external proxy server using clearOS linux with the squid application can be applied to a proxy router with a transparent proxy, so that clients to connect to the internet network at PT. Mega Maju Perkasa Bengkulu City must pass a proxy server first. The caching system can store caches of sites accessed by clients, from the tests that have been carried out there are data reports with 50 cache hits and 11% cache stored. In addition, the application of an external proxy server on the proxy router does not reduce the quality of service on network at PT. Mega Maju Perkasa Bengkulu City